Evaluating the use of reflective cafés in Specialist Community Practitioner and Specialist Community Public Health Nurse programmes. (2nd March 2023) - Boyle, Caroline; Logan, Sarah; Lavery, Joanna
Abstract : Background: Specialist Community Practitioner (SCP) and Specialist Community Public Health Nurse (SCPHN) students are required to evidence their competency by the use of reflective practice as part of the NMC proficiencies. A reflective café trilogy comprising of three reflective teaching sessions was developed and introduced into a university programme to support and encourage alternative methods for deeper reflection within this student group. Aim: It was important for educators to evaluate if a reflective café met the student's needs and understand the usefulness of a 'reflective café' as a technique to support the process of reflecting on practice. Methods: Evaluation was undertaken using an online questionnaire. Findings: Students evaluated if the reflective café was useful for their own development and identified that the number of sessions met their developmental needs. Conclusion: The potential to develop alternative methods to reflect was recognised and the team plan to develop other reflective processes to support students in the future.